2020
DOI: 10.3390/biology9040087
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Impact of Hepatic Steatosis on Response to Direct-Acting Antiviral Therapy in HIV–HCV Coinfection

Abstract: (1) Background: Direct-acting antiviral therapy for chronic hepatitis C virus (HCV) infection is associated with high sustained virologic response (SVR) and overcomes negative predictive factors, including steatosis, in patients without human immunodeficiency virus (HIV) coinfection. The impact of steatosis on SVR in patients with HIV–HCV coinfection is unknown. (2) Methods: A retrospective analysis of patients treated with direct-acting antivirals was performed. Demographic, laboratory and direct-acting antiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The presence of hepatic steatosis does not appear to affect high rates of achievement of virologic cure (sustained virological response at 12 weeks after end of treatment or SVR12) with the new direct-acting antiviral agents (DAAs). 220 The burden of SLD among HCV patients increased during treatment with DAAs, despite achievement of virologic cure, in a recent real-world cohort study by Trifan et al, 221 and those with SLD were observed to have a higher burden of advanced fibrosis. Additional prospective data on outcomes of persistent and new-onset SLD after SVR12 are needed to determine need for special screening and follow-up in this population.…”
Section: Hepatic Steatosis In Hepatitis C Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of hepatic steatosis does not appear to affect high rates of achievement of virologic cure (sustained virological response at 12 weeks after end of treatment or SVR12) with the new direct-acting antiviral agents (DAAs). 220 The burden of SLD among HCV patients increased during treatment with DAAs, despite achievement of virologic cure, in a recent real-world cohort study by Trifan et al, 221 and those with SLD were observed to have a higher burden of advanced fibrosis. Additional prospective data on outcomes of persistent and new-onset SLD after SVR12 are needed to determine need for special screening and follow-up in this population.…”
Section: Hepatic Steatosis In Hepatitis C Infectionmentioning
confidence: 99%
“…have reported results of a serial biopsy study with a mean follow‐up period of 6.5 years demonstrating that an initial finding of hepatic steatosis predicts increased stage of fibrosis and degree of inflammation at baseline but not their progression. The presence of hepatic steatosis does not appear to affect high rates of achievement of virologic cure (sustained virological response at 12 weeks after end of treatment or SVR12) with the new direct‐acting antiviral agents (DAAs) 220 . The burden of SLD among HCV patients increased during treatment with DAAs, despite achievement of virologic cure, in a recent real‐world cohort study by Trifan et al., 221 and those with SLD were observed to have a higher burden of advanced fibrosis.…”
Section: Clds Associated With Hepatic Steatosis (Slds)mentioning
confidence: 99%